Medical tourism: a new growth factor for Indian healthcare industry - Gupta, Manoj Kumar; Rajachar, Veena; Prabha, Chandra (International Journal of Research in Medical Sciences, 2017)
Epidemiological transition has given the opportunity to grow the traditional system of medicine across the world. Indian healthcare system which is already famous for providing quality of medical services at affordable cost as compared to developed countries took advantage of this opportunity and created a ‘basket of services’ by merging traditional medicines in existing allopathic system to attract patients across the borders. Government has made efforts in the direction of promoting medical tourism in the country and this has been fuelled by the private players both nationally and internationally. Recently this medical tourism has proved a major growth factor for expansion of Indian economy. However, the growth in this sector is underscored in terms of market share and cost advantages due to various challenges. There is also a need for proper diversion of revenue by a clear cut mechanism to strengthen the nation’s healthcare sector.